Scaling accountability through vertically integrated civil society pol icy monitoring and advocacy - Fox, Jonathan (IDS, 2016)
This working paper argues that the growing field of transparency, part icipation and accountability (TPA) needs a conceptual reboot, to addre ss the limited traction gained so far on the path to accountability. T o inform more strategic approaches and to identify the drivers of more sustainable institutional change, fresh analytical work is needed. Th is paper makes the case for one among several possible strategic appro aches by distinguishing between “scaling up” and “taking scale into ac count”. This proposition grounds an explanation of the vertical integr ation strategy, which involves multi-level coordination by civil socie ty organisations of policy monitoring and advocacy, grounded in broad pro-accountability constituencies. To spell out how this strategy can empower pro-accountability actors, the paper contrasts varied terms of engagement between state and society, proposing a focus on collaborat ive coalitions as an alternative to the conventional dichotomy between confrontation and constructive engagement. The paper grounds this dis cussion by reviewing the rich empirical terrain of existing multi-leve l approaches, summarizing nine cases – three each in three countries – to demonstrate what can be revealed when TPA initiatives are seen thr ough the lens of scale. It concludes with a set of broad analytical qu estions for discussion, followed by testable hypotheses proposed to in form future research agendas